Coexistence of MLCT Excited States of Different Symmetry upon Photoexcitation of a Single Molecular Species - Oviedo, Paola S.; Pieslinger, German E.; Baraldo, Luis M.; Cadranel, Alejandro; Guldi, Dirk Michael (Journal of Physical Chemistry C, 2019)
Photoexcitation of [Ru(tpy)(bpy)(mu-CN)Ru-(py)(4)Cl](2+) ([RuRu](2+)) at 387 nm results in the population of two (MLCT)-M-3 excited states of different symmetry that coexist on the nanosecond scale. Common to both states is an excited electron in a tpy-based orbital. Their configuration differs in the position of the hole. In one excited state, (3)MLCTz, the hole sits in an orbital parallel to the intermetallic axis allowing for a strong metal-metal electronic interaction. As a result, (3)MLCTz is highly delocalized over both metal centers and shows an intense photoinduced intervalence charge transfer (PIIVCT) NIR signature. In the other excited state, (3)MLCTxy, the hole is localized in an orbital perpendicular to the intermetallic axis and hence, significant intermetallic coupling is absent. This state shows no PIIVCT in the NIR and its spectrum is very similar to the one observed [Ru(tpy)(bpy)(CN)](+) reference. Both (MLCT)-M-3 excited states have nanosecond lifetimes. The intervening energy barrier for a hole reconfiguration between the two different (MLCT)-M-3 excited states offers the opportunity to exploit wave functions of different symmetry before either the interconversion between them or the decay to the ground state is operative.
CRIS-Team WoS Importer:2019-03-06